Knockdown of CENPW Inhibits Hepatocellular Carcinoma Progression by Inactivating E2F Signaling. (10th May 2021) - Zhou, Yajing; Chai, Hua; Guo, Lei; Dai, Zhongqiu; Lai, Jianming; Duan, Jianping; Liu, Yanting; Ding, Qian
Aim: This study aimed to evaluate the effects of centromere protein W (CENPW, also known as CUG2) in hepatocellular carcinoma (HCC). Methods: CENPW expression in HCC tissues and cells was detected by RT-qPCR assay. CCK-8 and colony formation assay were used to assess cell proliferation. Wound healing and Transwell assay was used to detect cell migration and invasion, respectively. The flow cytometry was used to analyze the cell cycle distribution and apoptosis. Results: CENPW expression was upregulated in HCC tissues and cells. Knockdown of CENPW inhibited cell proliferation, migration, and invasion and induced the G0/G1 phase arrest and cell apoptosis in HCC cells, which might involve the E2F signaling regulation. Conclusion: CENPW acted as an oncogenic role in HCC progression via activation E2F signaling. Our findings may provide new insights into the studying mechanisms of HCC.